Military and political security of the armed forces of Ukraine in 1991-1992 (archival material of State branch archives of the Ministry of Defence of Ukraine) - Levyk, Bogdan (Skhid, 2013)
Analysis of the first two years of the creation of the armed forces of Ukraine and directly involved in the process of the President, the Supreme Council and the Ministry of defence of Ukraine, Ukrainian officers-patriots. Are the specific facts of the struggle for the formation of the national army of independent Ukraine.